Modelling Backscattered Light in Fibre Optic Based on Light Propagation - M.H. Jamaludin; W.Z. Wan Ismail; F.S.N. Mohd Romzi; K.N. Zainul Ariffin; S. Suhaimi (Akademi Sains Malaysia, 2024)
Indexed by Scopus/MyCite